Pengaruh dana pihak ketiga dan non performing financing terhadap pembiayaan mudharabah pada bank umum syariah periode 2018-2020 - Anggraini, Noppia; Yarmunida, Miti; Julir, Nenan (STAI Auliaurrasyidin Tembilahan, 2025)
This research aims to determine and test the influence of third party funds (DPK) and non-performing financing (NPF) both partially and simultaneously on mudharabah financing in Islamic commercial banks in Indonesia for the 2018-2020 period. Using quantitative research with research objects at Sharia Commercial Banks. Purposive sampling was used to take samples for this research, resulting in a sample of 4 Sharia Commercial Banks. Data analysis techniques use multiple linear regression and hypothesis testing. Testing in this research uses SPSS 26. The research results show data that DPK has a significant effect on mudharabah financing. This is indicated by a significance value of 0.028 <0.05. NPF has no effect on mudharabah financing. This is indicated by a significance value of 0.193 > 0.05. DPK and NPF simultaneously influence mudharabah financing. This is indicated by a significance value of 0.034 <0.05.